NOVEL SÉRIAL CARITA SILAT ANJAR KARANGAN ACHMAD RUSTANDI : Ulikan Struktural Jeung Psikologi Humanistik - Purnamawati, - (2019)
NOVEL SÉRIAL CARITA SILAT ANJAR KARYA ACHMAD RUSTANDI (KAJIAN STRUKTURAL JEUNG PSIKOLOGI HUMANISTIK)1 Purnamawati2 ABSTRACT This research is based on the lack of children psychological integrity factor in which when they do children, it can affect themselves. The purpose of this research was to describe the structure of the story and humanistic psychology of the main character in the Carita Silat Anjar serial novel by Achmad Rustandi. The method used in this research was descriptive method with using qualitative approach, then the observation technique with using literature study, and in analyzing the discussion with using direct analysis technique. The source of data used in this research was Carita Silat serial novel by Achmad Rustandi. The structures contained in Carita Silat Anjar serial novel by Achmad Rustandi were themes, facts, and literature means. In the theme was found that serial novel narrated about the condition of colony life in the post-independence (Orde Baru 1966). In addition, there were the forward and backward plots in this serial novel. Whereas, the place and time settings support on the growth of the main character. Moreover, the social settings used in the story were upper and lower casts. The main character of the story was Anjar because he can attract a reader sympathy. The title was related to the content of the story. The point of view used was the third person who was knowledgeable. The writer uses a general basicity which is easy to be understood. The results of analysis from humanistic psychology, all of them fulfill the five basic level of human needs which appropriate with the transformation of Anjar's soul, only in the first novel which is not fulfilled in which it is in the need of self-esteem and the self-actualization in the main character. Based on the results of the overall analysis, it can be concluded that in the serial novel of Silat Anjar, there was a complete structure of the story. The main character (Anjar) in the story fills the five of basic level of human needs. Keywords: carita silat serial novel; humanistic psychology; and structure